STAT3 is required for MiR-17-5p-mediated sensitization to chemotherapy-induced apoptosis in breast cancer cells - Liao, Xing-Hua (Oncotarget, 2017)
Signal transducer and activator of transcription 3 (STAT3) controls cell survival, growth, migration, and invasion. Here, we observed that STAT3 exerted anti-apoptotic effects in breast cancer cells. On the other hand, miR-17-5p induced apoptosis in breast cancer cells, and overexpression of miR-17-5p sensitized MCF-7 cells to paclitaxel-induced apoptosis via STAT3. Overexpression of STAT3 in MCF-7 cells decreased paclitaxel-induced apoptosis, but STAT3 knockout abolished the miR-17-5p-induced increases in apoptosis. Finally, miR-17-5p promoted apoptosis by increasing p53 expression, which was inhibited by STAT3. These results demonstrate a novel pathway via which miR-17-5p inhibits STAT3 and increases p53 expression to promote apoptosis in breast cancer cells.